Effects of Stroke-ⅡOral Liquid on TLR4/MyD88/NF-κB Signal Pathway in Chemical Damaged PC12 Cells - Xinfu LIN; Ling SHI; Hengzhao ZHU; Sujuan CHEN; Xuehua ZHENG; Yiman WU (康复学报)
Objective:To investigate the effects of Stroke-Ⅱoral liquid on TLR4/MyD88/NF-κB signal pathway in chemical damaged PC12 cells.Methods:The chemical damaged PC12 cells model was established and treated by Stroke-Ⅱdrug-containing serum. All cells were divided into blank control group, model group, low dose group and high dose group. The cell proliferation was observed by MTT assay, the expression of TLR4, MyD88 and NF-κB mRNA were detected by RT-PCR, and their protein expressions were detected by Western Blot.Results:Compared with the blank control group, the proliferation of PC12 cells in the model group was decreased (P<0.01), and the expression of TLR4, MyD88 and NF-κB mRNA and protein were increased significantly (P<0.01, P<0.05). Compared with the model group, the proliferation of PC12 cells in low dose group and high dose group were increased (P<0.01, P<0.05), and the expression of TLR4, MyD88 and NF-κB mRNA and protein were decreased (P<0.01, P<0.05). Compared with the low dose group, the proliferation of PC12 cells in the high dose group was increased significantly (P<0.01, P<0.05), and the expression of TLR4, MyD88 and NF-κB mRNA and protein were decreased significantly (P<0.01, P<0.05).Conclusion:Stroke-Ⅱoral liquid could protect against chemical damage in PC12 cells via suppression of TLR4/MyD88/NF-κB signal pathway to regulate the inflammatory cascade response.